2011
DOI: 10.1007/s10008-011-1516-3
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication parameter-dependent morphologies of self-organized ZrO2 nanotubes during anodization

Abstract: Zirconia (ZrO 2 ) nanotubes have been synthesized using a facile anodizing process in organic electrolyte systems containing a low content of fluoride. The nanotube architecture evolution was recorded at different anodization periods (1-24 h) by scanning electron microscopy. A compact layer was found between the Zr substrate and its upper tubular layer after 1 h of anodization, whereas after further anodization for 3 h the compact layer disappeared. Meanwhile, ZrO 2 nanotubes turned to a uniform structure from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…This layer can be later removed by dissolving in water-containing electrolyte. This process was observed by Fang et al [33] who studied the nanotube evolution on Zr with time. They demonstrated that the compact layer rich in fluorine is formed between the metal and upper tubular layer after 1 h of anodization, and then, it disappears after 3 h. This experiment shows that the outer layer of nanotubes is fluoride-rich and it can be dissolved in the electrolyte.…”
Section: Polarization Measurementssupporting
confidence: 52%
“…This layer can be later removed by dissolving in water-containing electrolyte. This process was observed by Fang et al [33] who studied the nanotube evolution on Zr with time. They demonstrated that the compact layer rich in fluorine is formed between the metal and upper tubular layer after 1 h of anodization, and then, it disappears after 3 h. This experiment shows that the outer layer of nanotubes is fluoride-rich and it can be dissolved in the electrolyte.…”
Section: Polarization Measurementssupporting
confidence: 52%
“…After anodization, the samples had an amorphous structure which could be converted to tetragonal and monoclinic modifications after heating in a temperature range of 400-900°C. In their most recent study, Fang et al [34] followed an architecture evolution of nanotubes at different anodization points. They showed that while after 1 h, a compact layer rich in fluorine is formed between Zr and upper tubular layer, it disappears after 3 h. These results indicate that the outer layer of ZrO 2 nanotubes is fluoride-rich, and it can be dissolved in the surrounding electrolyte.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of zirconia nanotubes, the amorphous structure limits their applications area as a catalyst and photocatalyst [34]. Amorphous structure demonstrates the lack of stability in a solution of low pH level.…”
Section: Organic Electrolytesmentioning
confidence: 99%
See 2 more Smart Citations